Bulgaria : Selected Issues Paper. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper reviews recent developments in growth and employment in Bulgaria and highlights key constraints to growth suggested by cross-country competitiveness studies. Bulgaria's GDP has grown substantially since economic and financial stabilization in 1997. The global economic crisis had a major effect on Bulgarian growth and employment. After falling by 5 1\2 percent in 2009, real GDP has grown at a low rate, and by 2012 real GDP was still 3 percent short of its 2008 level. However, employment growth was negative during 2009-2012, and the first small uptick occurred only in 2013.